Insulated gate bipolar transistor reliability testing protocol for PV inverter applications. (16th January 2013) - Flicker, Jack; Kaplar, Robert; Yang, Benjamin; Marinella, Matthew; Granata, Jennifer
ABSTRACT To decrease the cost of ownership of photovoltaic systems, less costly and more reliable photovoltaic inverters must be developed. Insulated gate bipolar transistors are a significant cause of inverter failures and system inefficiencies, so a thorough understanding of their strengths and weaknesses with regards to inverters is necessary. This paper summarizes the current state of experimentation surrounding the use of IGBTs in photovoltaic inverters and discusses their construction, use, lifetime, and reliability of IGBTs regularly used in photovoltaic inverters. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.